The Social Interaction in Virtual Media - Madouni, Ali (Technium Social Sciences Journal, 2020)
As the virtual media emerged and disseminated immensely ; specifically in the last ten years of the twenty-first Century, through innumerable channels and virtually broadcasting pages, as strong equivalently as the traditional mass media in almost life critical domains and areas ; as a result and feature of the technological progress. The technology of the twenty- first Century gave to hands a wide reach and availability of information, it allows people and communities to participate even in producing and making influential public opinions towards local and international issues and topical; as ways of social interaction behind devices screens. Technology and changes create a sort of circumstantial adaptation which did not exist before. Furthermore and notably, the traditional mass media amid this advance; they specify regular corners and a considerable space for the virtual interactions of intellectual and popular society categories ; through the worldwide known media and interactive gates. and they give an increasing as well remarkable concern, and sometimes they are used as a referential and reliable base to these social interactions. Through this paper, we intended to spotlight on the interactive role of society in the virtual media, additionally, to expose to what extent can the virtually-made public opinions as well interactions can affect the statements and decisions in reality, on local and wider levels. .